Morphological, Mechanical and Interfacial Analysis of Vapour-Grown Carbon Fibres - Hattum, F. W. J. van (1997)
The diverse shapes in which vapour grown carbon fibres can be produced were studied using scanning electron microscopy and laser diffraction. Fibres with a cylindrical shape were characterised by tensile testing. It is shown that the Weibull distribution function is well adapted to interpret the fibres' strength data. On the other hand, the fragmentation method cannot be used to assess the quality of the interface of these fibres in polymeric matrix composites. This is due to the failure mode which is inherent to the inner structure of the vapour grown carbon fibres.